Evaluating the One-in-Five Statistic: Women's Risk of Sexual Assault While in College. Issue 4 (13th June 2017) - Muehlenhard, Charlene L.; Peterson, Zoë D.; Humphreys, Terry P.; Jozkowski, Kristen N.
Abstract : In 2014, U.S. president Barack Obama announced a White House Task Force to Protect Students From Sexual Assault, noting that "1 in 5 women on college campuses has been sexually assaulted during their time there." Since then, this one-in-five statistic has permeated public discourse. It is frequently reported, but some commentators have criticized it as exaggerated. Here, we address the question, "What percentage of women are sexually assaulted while in college?" After discussing definitions of sexual assault, we systematically review available data, focusing on studies that used large, representative samples of female undergraduates and multiple behaviorally specific questions. We conclude that one in five is a reasonably accurate average across women and campuses. We also review studies that are inappropriately cited as either supporting or debunking the one-in-five statistic; we explain why they do not adequately address this question. We identify and evaluate several assumptions implicit in the public discourse (e.g., the assumption that college students are at greater risk than nonstudents). Given the empirical support for the one-in-five statistic, we suggest that the controversy occurs because of misunderstandings about studies' methods and results and because this topic has implications for gender relations, power, and sexuality; this controversy is ultimately about values.